Design and Evaluation of Unidirectional Mucoadhesive Buccal Tablets of Diclofenac Sodium Using Different Polymers - Kavin, Pannerselvam; Mohankumar, Dhasaiyan; Sankar, Veintramuthu (Indian Journal of Pharmaceutical Education and Research)
Introduction: A mucoadhesive buccal drug delivery system is one of the novel methods to formulate the diclofenac sodium for increased bioavailability and bypass the hepatic first-pass metabolism, which would suppress the formation of peptic ulcers. The current focus of this research is to develop a mucoadhesive buccal tablet of diclofenac sodium and to evaluate its in vitro drug release profiles. Aim: The aim of this study is the design and evaluation of a unidirectional mucoadhesive buccal tablet of Diclofenac Sodium using different polymers. Materials and Methods: Mucoadhesive Diclofenac Sodium buccal tablets were prepared by direct compression method. Polymers used were Hydroxy Propyl Methyl Cellulose, Methyl Cellulose, Sodium Carboxy Methyl Cellulose, Carbopol, Sodium alginate and Ethyl Cellulose used as an impermeable backing layer. Ethyl Cellulose helps with the unidirectional drug release of the buccal tablet. The evaluation parameters and mucoadhesive strength evaluations, along with in vitro assessments, were conducted to analyse the performance of the formulations. Results: The formulation f4 was chosen as the best formulation based on the results. All physicochemical parameters were in compliant with the Indian Pharmacopeia. In vitro drug release from the buccal tablet was 63.36% at the 5th hour. The swelling index of the tablet was 65% at 30 min. The adhesion time was more than 6 hr. Surface pH is suitable for oral pH. f4 follows the mixed-order release of both first order and non-fickian (n<0.89). The Carbopol-containing tablet showed a peak force of 0.108 N and a positive work of adhesion of 0.145 N.sec, indicating stronger mucoadhesion compared to the normal tablet, which had a peak force of 0.0508 N and a negative work of adhesion of -0.241 N.sec. Conclusion: These findings led to the development of a product that could help to prevent the first pass effect of Diclofenac Sodium and to enhance its bioavailability.
Keywords: Buccal tablet; Mucoadhesive; Adhesion time; Swelling index; Carbopol; Surface pH